Intrauterine exposure to preeclampsia does not impair vascular health in children - Benjamin J. Varley; Benjamin J. Varley; Amanda Henry; Amanda Henry; Amanda Henry; Amanda Henry; Lynne Roberts; Lynne Roberts; Gregory Davis; Gregory Davis; Michael R. Skilton; Michael R. Skilton; et al. (Frontiers Media S.A., 2022)
Background and objectivesPreeclampsia is a serious multisystem blood pressure disorder during pregnancy that is associated with increased long-term risk of cardiovascular disease to the mother and offspring. We investigated the vascular health of children exposed to intrauterine preeclampsia.Materials and methodsThis was a cross-sectional study of offspring in a prospective cohort of women with complications during pregnancy. Children aged between 2 and 5 years [median age 4.7 (2.8, 5.1) years] exposed to intrauterine preeclampsia (n = 26) or normotensive controls (n = 34), were recruited between July 2020 and April 2021. Vascular health was assessed by measuring aortic intima-media thickness and pulse wave velocity. Univariate generalized linear regression models were used to explore associations between vascular measurements and explanatory variables.ResultsChildren exposed to preeclampsia had a lower body mass index at assessment (15.5 vs. 16.2 kg/m2, p = 0.04), birth weight (2.90 vs. 3.34 kg, p = 0.004), gestational age at birth (37.5 vs. 39.4 weeks, p < 0.001) and higher frequency of preterm birth (27% vs. 6%, p = 0.02). There were no differences in vascular health between children exposed to preeclampsia vs. controls (mean aortic intima-media thickness 0.575 mm vs. 0.563 mm, p = 0.51, pulse wave velocity 4.09 vs. 4.18 m/s, p = 0.54) and there were no significant associations in univariate analyses.ConclusionsThere were no major adverse differences in vascular health which contrasts with existing studies. This suggests exposure to intrauterine preeclampsia may result in a less severe cardiovascular phenotype in young children. While reassuring, longitudinal studies are required to determine if and when exposure to intrauterine preeclampsia affects vascular health in children.